Thailand wine tourism: A dream or a reality? - Chong, Daniel Ka Leong * (Taylor & Francis, 2017)
Conventionally, wine tourism is mainly popular in Australia, New Zealand, South Africa and the Europe regions. Interestingly, Thailand despite being a young wine producing country has emerged as a potential wine tourism provider within the Southeast Asia regions.This research aimed to evaluate the competitiveness of Thailand wine tourism’s within its regional growth. Porter’s Four Diamond Model was used as a tool to assess this industry competitiveness. Three wineries in Thailand were visited and qualitative approaches comprising interview and observation were utilized as the means of data collection. Triangulation was used to analyse the reliability of the data gathered. The finding showed that wine tourism in Thailand was still an infant industry as most tourists and tourism operators were still not aware of the product offered. However, the wineries themselves had already owned the competency to serve the market.